Pengembangan produk teh kulit buah kopi dari tiga klon kopi robusta - Analianasari Analianasari; Dayang Berliana; Eko Win Kenali; Meinilwita Yulia (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Coffee skin is a waste from green coffee production as much as 40-45% which has the potential as a source of natural antioxidants. The diversity of local Robusta coffee clones in West Lampung as raw materials for the processing of coffee products provides a variety of coffee skins which are thought to have strong antioxidant activity which is useful as a functional drink for coffee skin tea (cascara).The aims of the study werestudy aimed of the study were to identify the sweetness level of coffee cherries skin from three local coffee robusta clones (rope, huerona, and srintil), identify antioxidant activity, test consumer preferences, and calculate the added value of coffee skin tea (cascara). The research method uses DPPH antioxidant activity analysis, consumer preference test (organoleptic hedonic test), and the calculation of added valueadded value calculation using the Hayami method. The results showed that the antioxidant activity of the Rope clone had strong antioxidant activity, the cascara drink on the level of aroma, taste, and liking for cascara tea found no difference between samples based on analysis of variance, but. Still, the cascara drink from the Rope clone had a darker color. The added value generated by the cascara is IDR 27,941 per kilogram of raw materials used